Development of a Radially Coupled Wireless Charging System for Torpedo-Shaped Autonomous Underwater Vehicles - Mingwei Lin; Ri Lin; Dejun Li; Runtian Duan (Journal of Marine Science and Engineering, 2023)
Spiral coaxial coils are widely used in wireless charging systems for autonomous underwater vehicles (AUVs). However, these coils can generate axial electromagnetic interference that may adversely affect the electronic components contained within the AUV. In order to overcome this issue, this paper introduced a pair of radially coupled coils which implement distributed ferrite cores. The mathematical model of the curly coils was derived, and its geometry parameters were optimized through the use of genetic algorithms. ANSYS Maxwell was used to analyze and optimize the layout of the ferrite cores. A prototype of the AUV wireless charging system was presented, demonstrating a maximum efficiency of 94% at 2.2 kW in salt water. The rotation adaptivity of the system was also tested, revealing stable output performance within the possible roll-angle variations of the AUV.